Nonconsecutive- versus consecutive-day high-intensity interval training in cyclists - Gross, M.; Swensen, T.; King, D. (Medicine & Science in Sports & Exercise, 2007)
Purpose: We compared the effects of a high-intensity interval training (HIT) program completed on three consecutive or nonconsecutive days per week for 3 wk on VO2peak, peak aerobic power output (PPOa), and 5-km time trial (TT5k) performance in trained cyclists.